From 'boat to plate': Creating value through sustainable fish Supply Chain visibility - Cardoso, U.; I. Almeida; Silva, J.; Ferreira, L. (Proceedings of The XXXIV International Conference on Industrial Engineering and Management (ICIEM 2013), 2013)
Despite companies have traditionally considered KPIs related to price, quality and flexibility, the increase of environmental pressures has begun to demand attention and so, improvement of suppliers’ environmental performance. Better management of marine resources, development of good practices and visibility were addressed in this research. The introduced framework was developed from analysing environmental management practices in a retailer exploratory case, by following a triple bottom line approach to fine tuning corporate responsibility. Then, the paper outlined recommendations towards sustainable operations, as regards: developing voluntary self-certification towards eco-labelling based on third party; using IT, as a visibility promoter and so, as a leverage for traceability, collaboration and trust across the chain of custody; designing customised policies to deal with different consumer profiles and so, assuring their loyalty by adjusting consumer campaigns; educating consumers as seafood demand regulators. Finally, improvements in Greenpeace evaluation were documented, and profit increase was expected.